Characterization of a Novel Monoclonal Antibody for Serine-129 Phosphorylated α-Synuclein: A Potential Application for Clinical and Basic Research - Liu, Weijin; Zhang, Qidi; Xing, Hao; Gao, Ge; Liu, Jia; Huang, Yue; Yang, Hui (Frontiers in Neurology, 2022)
The Lewy bodies (LBs) are the pathological hallmark of Parkinson's disease (PD). More than 90% of α-synuclein (α-syn) within LBs is phosphorylated at the serine-129 residue [pSer129 α-syn (p-α-syn)]. Although various studies have revealed that this abnormally elevated p-α-syn acts as a pathological biomarker and is involved in the pathogenic process of PD, the exact pathophysiological mechanisms of p-α-syn are still not fully understood. Therefore, the development of specific and reliable tools for p-α-syn detection is important. In this study, we generated a novel p-α-syn mouse monoclonal antibody (C140S) using hybridoma technology. To further identify the characteristics of C140S, we performed several in vitro assays using recombinant proteins, along with ex vivo assays utilizing the brains of Thy1-SNCA transgenic (Tg) mice, the preformed fibril (PFF)-treated neurons, and the brain sections of patients with PD. Our C140S specifically recognized human and mouse p-α-syn proteins both in vitro and ex vivo, and similar to commercial p-α-syn antibodies, the C140S detected higher levels of p-α-syn in the midbrain of the Tg mice. Using immunogold electron microscopy, these p-α-syn particles were partly deposited in the cytoplasm and colocalized with the outer mitochondrial membrane. In addition, the C140S recognized p-α-syn pathologies in the PFF-treated neurons and the amygdala of patients with PD. Overall, the C140S antibody was a specific and potential research tool in the detection and mechanistic studies of pathogenic p-α-syn in PD and related synucleinopathies.